2012
DOI: 10.3109/0886022x.2012.745153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Renal Function on Left Ventricle and Analysis of Related Factors in Patients with Hemodialysis

Abstract: Background: Left ventricular hypertrophy (LVH) and systolic dysfunction would predict the mortality of patients undergoing maintenance hemodialysis. The cause of LVH is usually related to the increase of total peripheral vascular resistance and overloading volume. The presence of residual diuresis enables greater control of the volume. This study evaluated the effects of residual renal function (RRF) on the left ventricle and analyzed the related factors involved in hemodialysis patients. Methods: A total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
(35 reference statements)
2
13
0
1
Order By: Relevance
“…Furthermore, there was a significant interaction between residual daily UVol and treatment effect on IDWG in both trials (for TIFL it was significant in the Daily Trial only). In accordance with already published results [17,18], the presence of high baseline urinary volume may have also reduced the effects of frequent HD on LVM change [24,25] .…”
Section: Residual Uvol and Consequences On Studied Outcomessupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, there was a significant interaction between residual daily UVol and treatment effect on IDWG in both trials (for TIFL it was significant in the Daily Trial only). In accordance with already published results [17,18], the presence of high baseline urinary volume may have also reduced the effects of frequent HD on LVM change [24,25] .…”
Section: Residual Uvol and Consequences On Studied Outcomessupporting
confidence: 78%
“…Reduction of ECF is known to be followed by a reduction in blood pressure and consequently LVM [24,25] . In the Daily Trial, an association was found between change in predialysis SBP over the 12-month study period and change in LVM (slope estimate 6.6 g per 10 mm Hg in the group receiving 3/week HD and 10.1 g per 10 mm Hg in the group assigned to frequent HD) [17] .…”
Section: Sbp and Reduction Of Extracellular Volume Expansionmentioning
confidence: 99%
“…Studies have showed that RRF had beneficial effects on LV hypertrophy and fluid removal. 22 Loss of RRF led to fluid overload which enhanced the burden of LV and contributed to LV dysfunction. Wen et al showed that higher peritoneal dialysate glucose concentration (PDGC) was significantly associated with low RRF and significantly associated with higher allcause and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, increasing evidence suggests that the preservation of RUV contribute in favorable way on the predictors of mortality in HD such as hypervolemia [11], left ventricular hypertrophy (LVH) and congestive heart failure [12, 13], heart rhythm disorders [14] and ischemic strokes [15]. In fact, Ma and Ding [16] found, in a case-control study, that the frequency of LVH and systolic dysfunction was significantly lower in patients with preserved RRF (RUV ≥ 200 ml/day) compared to those having lost RRF (RUV ˂ 200 ml/day). Furthermore, similar findings with respect to plasma concentration of B-type natriuretic peptide (BNP) and homocysteine were also reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Ma and Ding [16] found, in a case-control study, that the frequency of LVH and systolic dysfunction was significantly lower in patients with preserved RRF (RUV ≥ 200 ml/day) compared to those having lost RRF (RUV ˂ 200 ml/day). Furthermore, similar findings with respect to plasma concentration of B-type natriuretic peptide (BNP) and homocysteine were also reported [16]. …”
Section: Introductionmentioning
confidence: 99%